ANALISIS SEMIOTIKA PADA TRILOGI ALINA DALAM ANTOLOGI CERPEN SEPOTONG SENJA UNTUK PACARKU KARYA SENO GUMIRA ADJI DARMA - Sudrajat, Rochmat Tri; Muhamad, Fadel (IKIP Siliwangi, 2020)
This article discusses a surrealist short story. The approach used in this study is Pierce's semiotics approach, which is to discuss the signs in the short story anthology entitled